Effect of a 3-Weeks Training Camp on Muscle Oxygenation, V˙O2 and Performance in Elite Sprint Kayakers - Paquette, Myriam; Bieuzen, François; Billaut, François (Frontiers in Sports and Active Living, 2020)
Purpose Peripheral adaptations, as assessed via near-infrared spectroscopy (NIRS) derived changes in muscle oxygenation (SmO2), are good predictors of sprint kayak performance. Therefore, the goal of the present study was to assess changes in SmO2 and V̇O2 following a training camp in elite sprint kayakers to evaluate if the training prescribed elicits peripheral adaptations, and to assess associations between training-induced changes in physiological responses and performance. Methods Eight male elite sprint kayakers, members of the Canadian National Team, performed a 200-m and 1000-m on-water time trial (TT) before and after a 3-week winter training camp. Change in performance, V̇O2 and SmO2 of the biceps brachii were assessed in relation to training load. Results Training load and intensity were increased by 20% over the course of the training camp, which resulted in a 3.7±1.7% (ES -1.2) and 2.8±2.4% (ES -1.3) improvement in 200-m and 1000-m performance, respectively. Performance improvement in the 200-m was concomitant to a reduced SmO2, an increased V̇O2peak and an increased reoxygenation rate after the TT. The 1000-m TT performance improvement was concurrent with a reduced SmO2 in the last half of the TT and an increased V̇O2 in the first minute of the TT. Conclusion Our results strongly suggest that peripheral skeletal muscle adaptations occurred in these athletes with the proposed training plan. This further attests the benefit of using portable NIRS as a monitoring tool to track training-induced adaptations in muscle oxygen extraction in elite athletes.